(untitled) (Revista Inclusiones, 2018)
The article explores the role of sport in the value orientations of Russian youth. Sport is an important part of modern culture; it embodies a number of values inherent in modern culture in general, for example, the value of success. In modern societies, sport not only involves thousands of people in specific behavioral practices, but also changes values, standards of behavior, and lifestyle beyond the realm of professional sport. At the same time, the recognition of the importance of sport and the values embodied in it does not always lead to the involvement of the individual in sport. On the other hand, involvement in sport activities and communities interested in sport does not always imply positive social activity. In other words, it can be said about passive and active acceptance of the value of sport, and sport itself appears to be a contradictory phenomenon in terms of value perception.